1998
DOI: 10.1164/ajrccm.157.5.96-10089
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Nitric Oxide Versus Conventional Therapy

Abstract: A randomized, controlled clinical trial was performed with patients with acute respiratory distress syndrome (ARDS) to compare the effect of conventional therapy or inhaled nitric oxide (iNO) on oxygenation. Patients were randomized to either conventional therapy or conventional therapy plus iNO for 72 h. We tested the following hypotheses: (1) that iNO would improve oxygenation during the 72 h after randomization, as compared with conventional therapy; and (2) that iNO would increase the likelihood that patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
113
2
14

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(132 citation statements)
references
References 46 publications
3
113
2
14
Order By: Relevance
“…In randomized clinical trials, inhaled nitric oxide was associated with a transient improvement in oxygenation in adults with ARDS without any survival benefit. [16][17][18][19][20] In a systematic review and meta-analysis of patients with acute lung injury or ARDS from 12 trials, inhaled nitric oxide was associated with modest improvements in oxygenation (13% increase in P aO 2 /F IO 2 until days 3-4 of administration), no effect on mean pulmonary artery pressure, and no effect on survival or duration of mechanical ventilation. 21 Period 1 is defined as prior to the start of the epoprostenol infusion, and period 2 is defined as during the epoprostenol infusion.…”
Section: Discussionmentioning
confidence: 99%
“…In randomized clinical trials, inhaled nitric oxide was associated with a transient improvement in oxygenation in adults with ARDS without any survival benefit. [16][17][18][19][20] In a systematic review and meta-analysis of patients with acute lung injury or ARDS from 12 trials, inhaled nitric oxide was associated with modest improvements in oxygenation (13% increase in P aO 2 /F IO 2 until days 3-4 of administration), no effect on mean pulmonary artery pressure, and no effect on survival or duration of mechanical ventilation. 21 Period 1 is defined as prior to the start of the epoprostenol infusion, and period 2 is defined as during the epoprostenol infusion.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, subsequent clinical trials reported disappointing outcome results. Inhaled NO therapy did not affect the duration of ventilatory support or mortality in 2 single-center pilot trials 61,62 and in 3 multicenter randomized trials. [63][64][65] Because most patients dying from acute respiratory distress syndrome suffer from multiple organ failure, it is unlikely that the beneficial effects of a lung-selective therapy such as inhaled NO will alter the overall survival rate.…”
Section: Inhaled No and Acute Respiratory Distress Syndromementioning
confidence: 99%
“…Because of the vasodilatory effects of NO, inhalation of this agent has been used as a therapeutic approach to decrease the pulmonary vascular resistance in well-ventilated, ie, NO-accessible lung areas, and thereby improve oxygenation in patients with acute respiratory distress syndrome (ARDS) (Michael et al, 1998;Payen, 1998;Troncy et al, 1998). Unfortunately, NO inhalation, although initially improving gas exchange, did not lead to sustained improvement of oxygenation compared with conventional therapy in the hitherto performed controlled studies (Michael et al, 1998;Payen, 1998).…”
mentioning
confidence: 99%
“…Unfortunately, NO inhalation, although initially improving gas exchange, did not lead to sustained improvement of oxygenation compared with conventional therapy in the hitherto performed controlled studies (Michael et al, 1998;Payen, 1998). Nonvasodilation-related effects of inhaled NO, currently not well understood, have been suggested to explain this finding.…”
mentioning
confidence: 99%